Association of Blood Lipid Profile Components with White Matter Hyperintensity Burden in Cerebral Small Vessel Disease - Li, Shanshan; Wang, Yunchao; Yu, Lulu; Gao, Yuan; Yang, Yinghao; Zhu, Hanghang; An, Lu; Yuan, Wenxin; Wu, Jinghao; Zong, Ce; Xu, Yuming; Li, Yusheng (Current Neurovascular Research, 2023)
Background: Cerebral small vessel disease (CSVD) refers to a common cerebrovascular disease and white matter hyperintensities (WMHs) constitute a typical feature of CSVD. However, there has not been a large number of studies investigating the relationship between lipid profile components and WMHs. Methods: Altogether, 1019 patients with CSVD were enrolled at the First Affiliated Hospital of Zhengzhou University between April 2016 to December 2021. Baseline data were collected for all patients, including demographic characteristics and clinical data. WMH volumes were evaluated by two experienced neurologists using the MRIcro software. Multivariate regression analysis was used to investigate the relationship among the severity of WMHs, blood lipids and common risk factors. Results: Altogether, 1019 patients with CSVD were enrolled, including 255 in the severe WMH group and 764 in the mild WMH group. After including age, sex and blood lipids to construct a multivariate logistic regression equation, we observed that the severity of WMHs was independently predicted by low-density lipoprotein (LDL), homocysteine level and history of cerebral infarction. Conclusion: We used WMH volume, a highly accurate measure, to assess its relationship with lipid profiles. The WMH volume increased with a decrease in LDL. This relationship was more significant, especially among the subgroups of patients aged <70 years and men. Patients with cerebral infarction and higher homocysteine levels were more likely to have higher WMH volumes. Our study has provided a reference for clinical diagnosis and therapy, especially for discussing the role of blood lipid profiles in the pathophysiology of CSVD.
Keywords: blood lipid profiles